Sentinel Lymph Node Biopsy May Prevent Unnecessary Axillary Dissection in Patients with Inflammatory Breast Cancer Who Respond to Systemic Treatment - (:unkn) unknown (KARGER, 2021)
Background and Objectives: Inflammatory breast cancer (IBC) is a rare and aggressive breast cancer treated up-front with systemic treatment. Both breast-conserving surgery and sentinel lymph node biopsy (SLNB) are controversial issues in the management of IBC. In this study, we aimed to assess the feasibility of SLNB in pathologically proven node-positive IBC patients. Methods: All patients with a histopathological diagnosis of IBC and biopsy-proven metastatic axillary lymph nodes underwent systemic treatment. Patients with a complete clinical response in the axilla who underwent SLNB followed by standard axillary dissection were analyzed. Results: The study consisted of 25 female patients. The identification rate (IR) and the false negativity rate (FNR) were 17/25 and 2/10, respectively. Overall, 9/25 and 7/25 of patients had a complete pathological response (pCR) in the breast and axilla after systemic treatment, respectively. Although the pCR in the axilla was 2/4 in nonluminal HER2-positive patients, the highest IR 4/4 and the lowest FNR 0/2 were determined in these patients. In triple-negative patients, however, the IR was 2/4 and the FNR was found to be 0/2. Conclusions: SLNB may be considered in selected axilla-downstaged IBC patients including patients with a pCR with HER2-positive and triple-negative tumors. Axillary dissection may be, therefore, omitted in those with negative SLNs.
Keywords: Sentinel lymph node biopsy; Inflammatory breast cancer; Neoadjuvant systemic treatment; HER2-positive breast cancer; Triple-negative breast cancer; NEOADJUVANT CHEMOTHERAPY; THERAPY